European regional science: the strength of gaps in our knowledge (review of the ERSA 2009 Lodz Congress papers) - Alexander Pelyasov (European Regional Science Association (ERSA), 2010)
To create state of the art picture of the European regional science review of Lodz Congress papers will be combined with the materials of our previous reviews of reports from the last four Congresses, and our analysis of hundreds of papers published in the major journals of regional science for the last 10-12 years. We will characterize the peculiarities of major national schools in European regional science, its strengths and weaknesses; describe the specific intellectual manner of the major leaders of European regional science; reveal real and potential bridges between regional science and neighboring fields of knowledge - cognitive science, institutional economics in particular. In the focus of this year review will be gaps of our knowledge in Regional science and how they can be filled with our collective efforts.
Keywords: 330